Examine online learning: The influence of cost readiness on Modern Education - Areche, Franklin Ore (International Journal of Humanities and Education Development (IJHED), 2022)
The primary goal of this research is to examine and analyse the cost readiness factor as it relates to e-learning deployment. The study will look at the cost efficiency and cost readiness factors that influence the successful adoption of an e-learning system, and propose prospective and long-term solutions that would go a long way toward overcoming cost obstacles in the future. The researchers used a quantitative research method to determine the cost readiness of e-learning implementation. The participants in this study were 219 participants from several private universities. The results demonstrated that cost preparedness has a large predictive value for e-learning and will have a direct positive relationship with it. The survey questions may not necessarily generalize to the greater community of instructors and administrative personnel at private colleges, which is one of the study's limitations.